Using integrated technology to create quality care for older adults: a feasibility study. (3rd July 2019) - Tarraf, Rima C.; Suter, Esther; Arain, Mubashir; Birney, Arden; Boakye, Omenaa; Boulanger, Pierre; Sadowski, Cheryl A.
ABSTRACT: Purpose: Slow changes in older adults' health status are often not detected until they escalate. Our aim was to understand if e-technology can enhance the safety and quality of older adult care by detecting changes in health status early. Methods: E-technology was implemented with 30 seniors in an assisted living facility. We used wireless devices to monitor blood pressure, oxygen saturation, weight, and hydration. This 1-year feasibility study included: a readiness assessment, procuring devices, developing an alert software, training staff, and weekly monitoring for several months. Results: Analysis of service utilization data showed no significant differences in number of emergency or hospital visits between the intervention and control group. Qualitative data suggested residents were satisfied with the e-technology. Among staff, several saw value in weekly monitoring, however staff emphasized the need for devices to be suitable for older adults. Conclusion: It is imperative that researchers work with facilities to ensure there is value-added in implementing new technology. Staff feedback helped fine-tune devices, training materials, and measurement process. It took longer than anticipated to procure suitable devices, set up the software, and recruit residents, thus limiting data collection. Future studies should dedicate more time to implementation and propose longer timelines.